Processos de referenciação e orientação argumentativa: uma proposta de análise em redações do Saresp - Souza, Fátima Aparecida de (2014)
This work is in the line of investigation named Reading, Writing and Teaching from Portuguese Postgraduate Studies Program from the Pontifícia Universidade Católica de São Paulo (PUC-SP). The theme is about referentiation processes and their relationships with argumentative orientation observed in compositions written by grade students of high school for the School Evaluation and Efficiency System of the State of São Paulo (Saresp). Our hypothesis is that the processes of deictic and anaphoric referentiation contribute to the development of textual argumentative orientation. In this sense, we establish as general aim investigate the contributions referentiation processes for the development of argumentative compositions produced for Saresp. In order to achieve this general aim, we define specific aims: identify, describe and analyze deictic and anaphoric operations; establish relationships between these operations and argumentative orientation; reflect on teaching Portuguese language based on these relationships. To support this research, we are based on contributions from Mondada and Dubois (2003), Choi (2000a, 2000b, 2003, 2005, 2006), Apothéloz (2003), Marcuschi (2005, 2008), Koch (2005), Marquesi (2007), Mosca (2004), Perelman and Olbrechts-Tyteca (2005), Aristotle (1996), Ferreira (2010), Ducrot (1981), Guimarães (2007), Charaudeau (2007) and Adam (2008). The corpus is consisted of six texts selected from a universe of 110 opinion articles written by students of the 3rd grade of high school from a public state school in the state of São Paulo to Saresp 2010. In relation to the results obtained, we find that: a) deitics and anaphoras are contents of statements that work as arguments as well as conclusion to such arguments; b) deitics and anaphoras, when have argumentative strength or persuasive value, can explain the meaning of the enunciative way according to the meanings the writer intended to produce